(untitled) (Philology, 2026)
Scaldic poetry is one of the main genres in Old Norse literature and a product of an ancient oral tradition in the Nordic area. It is unique in terms of form, structure and themes and has no analogue in European literature in the period between the 9th and 11th century. The paper discusses the use of specific means of expression and metric systems in Scaldic poetry. The literary themes in Scaldic poems derive from reality and actual historic events. They are varied, such as the heroic deeds and the price the main characters have to pay for them, the value of honour and fame. As a whole they are a reflection of the way of thinking and living of the people in the North. In this respect Scaldic poems turn out to be the living memory of these old gone times, delivered as coded messages over time.